2007
DOI: 10.1089/acm.2006.5293
|View full text |Cite
|
Sign up to set email alerts
|

Sasangin Diagnosis Questionnaire: Test of Reliability

Abstract: All the categories of SDQ can be accepted as being reliable scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 3 publications
0
28
0
Order By: Relevance
“…The Questionnaire for Sasang Constitution Classification (QSCC) is a program widely used in this field, and it has been shown that physical constitution changes according to appearance, character, common symptoms, and reactions to certain foods. More than 30 papers have been published since 1991 in this field, and many scientific methodologies have been introduced from consultations with psychologists, Korean language experts, and statisticians [14][15][16][17][18][19][20][21].…”
Section: Questioning Diagnosis (Interview)mentioning
confidence: 99%
“…The Questionnaire for Sasang Constitution Classification (QSCC) is a program widely used in this field, and it has been shown that physical constitution changes according to appearance, character, common symptoms, and reactions to certain foods. More than 30 papers have been published since 1991 in this field, and many scientific methodologies have been introduced from consultations with psychologists, Korean language experts, and statisticians [14][15][16][17][18][19][20][21].…”
Section: Questioning Diagnosis (Interview)mentioning
confidence: 99%
“…According to the SCM perspective, human beings can be classified into four constitutional types: Tae-Yang (TY), So-Yang (SY), Tae-Eum (TE), and So-Eum (SE). These types have typically distinct characteristics in terms of equilibrium among internal organ functions, external appearance, personality traits, and their responses to drugs and treatment 1, 2, 3, 4, 5, 6. The constitutional approach of SCM has received attention because of its utility for individualized therapy; SCM can help patients avoid unnecessary side-effects while increasing efficacy by prescribing the appropriate medicine for each constitutional type 1, 2.…”
Section: Introductionmentioning
confidence: 99%
“…The constitutional approach of SCM has received attention because of its utility for individualized therapy; SCM can help patients avoid unnecessary side-effects while increasing efficacy by prescribing the appropriate medicine for each constitutional type 1, 2. Before prescription, therefore, the patient's constitution is diagnosed in a noninvasive way based on an analysis of factors, such as external appearance, voice, and personality traits, by SCM doctors’ five senses 5, 6. Facial features, in particular, have been firmly regarded by SCM doctors as representative and reliable characteristics for distinguishing among Sasang constitutional (SC) types 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous questionnaires, such as the Yin Deficiency and the Sasang Diagnosis Questionnaires, are good examples of this. 10,11 In pathologic pattern identification, there exist both detailed TCM patterns such as ''qi stagnation transforming into Heat with Dampness accumulation'' 12 and also broader pattern categories such as yin, yang, Cold, Heat, Excess, and Deficiency. Some advantages of this broad approach are that it may be easier for practitioners to agree on the fundamental characteristics than on more detailed evaluations and that it captures the important and essential elements of TCM diagnosis.…”
Section: Introductionmentioning
confidence: 99%